Crop rotation with Species Diversification During Off-season Impact the Nutrient Cycling in No-tillage System - Côrt, Andressa Selestina Dalla [UNESP]; Pacheco, Leandro Pereira; Guedes, Thaís Rodrigues Magalhães; Silva, Laércio Santos; Greco, Tassia Maira; de Macedo, Kamila Silva; Batista, Eder Rodrigues; de Souza, Edicarlos Damacena; da Silva, Izabela Aline Gomes; Crusciol, Carlos Alexandre Costa [UNESP] (Springer Nature, 2025)
This study aimed to investigate the potential impact of annual and off-season crops on primary macronutrient (N, P and K) cycling and soybean yield in no-tillage system (NTS) in the Brazilian Cerrado. Soybean was sown in the summer season in all systems from 2014 to 2015 and 2018 to 2019 under a randomized block design with the following treatments: MC1: monocropped 1 (conventional tillage); MC2: monocropped 2 (fallow under no-tillage); CS1: crop succession 1 (Crotalaria spectabilis); CS2: crop succession 2 (Pennisetum glaucum); CS3: crop succession 3 (Urochloa ruziziensis); CS4: crop succession 4 (Cajanus cajan); IC1: intercropped 1 (corn + C. spectabilis); IC2: intercropped 2 (corn + U. ruziziensis); MIX (C. spectabilis + P. glaucum + U. ruziziensis + C. cajan). Accumulation, release of nutrients andaboveground mass were evaluated during the cover crops senescence at 0,15, 30, 60, 90 and 120 days after desiccation. The soybean grain yield was evaluated at the harvest. The U. ruziziensis with corn and MIX released 70% of the N at 60 days after desiccation and accumulated 138.80 kg of N ha–1 at the senescence, increasing by up to 500% the phytomass accumulation efficiency in the off-season compared to fallow. The cover crop in the MIX system increased K cycling due to higher accumulation rates (187 kg ha–1) with 95% of K released to the soil via aboveground phytomass. The U. ruziziensis intensified P cycling in diversified systems due to high concentration (75 kg ha–1) in aboveground mass during the off-season, with 95% of P released to the soil up to 60 days after soybean sowing. Soybean yields were 20% higher with cover crops, especially with C. spectabilis. Diversification of annual and off-season cover crops is a sustainable strategy to improve nutrient cycling and soybean yield in an NTS system in the Brazilian Cerrado.